2021
DOI: 10.1111/apa.16075
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing during the COVID‐19 pandemic resulted in a marked decrease in hospitalisations for bronchiolitis

Abstract: Bronchiolitis is the most common acute viral infection of the lower airways in infants and the main cause of hospitalisation and death from viral infections in western countries. The worldwide COVID-19 pandemic has led to most countries adopting social distancing measures and population movement restrictions to reduce transmission of the severe acute respiratory syndrome coronavirus 2 infection. During the 2020-2021 winter season, social distancing and mask use altered the spread of common viral respiratory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
(15 reference statements)
3
15
0
Order By: Relevance
“…Several factors can be involved in this epidemiological change: public health measures such as social distancing, travel restrictions, compulsory use of face masks and hand sanitisation, likely reduced exposure and suppressed interhuman transmission of SARS-CoV-2 and other viruses. Rhinovirus was the primary pathogen isolated in our series, as already reported in other studies performed during the SARS-CoV-2 pandemic 19 20. The observed frequency of rhinovirus is consistent with the average circulation of the virus, which has its peak during early fall, and to a lesser extent, during spring 21 22.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several factors can be involved in this epidemiological change: public health measures such as social distancing, travel restrictions, compulsory use of face masks and hand sanitisation, likely reduced exposure and suppressed interhuman transmission of SARS-CoV-2 and other viruses. Rhinovirus was the primary pathogen isolated in our series, as already reported in other studies performed during the SARS-CoV-2 pandemic 19 20. The observed frequency of rhinovirus is consistent with the average circulation of the virus, which has its peak during early fall, and to a lesser extent, during spring 21 22.…”
Section: Discussionsupporting
confidence: 90%
“…Rhinovirus was the primary pathogen isolated in our series, as already reported in other studies performed during the SARS-CoV-2 pandemic. 19 20 The observed frequency of rhinovirus is consistent with the average circulation of the virus, which has its peak during early fall, and to a lesser extent, during spring. 21 22 It has been shown that while face masks can prevent transmission of human coronaviruses and influenza viruses, they do not reduce the transmission of droplets and aerosols containing rhinoviruses.…”
Section: Discussionsupporting
confidence: 76%
“…Our results also showed a considerable decrease in urgent admissions to the neonatal ward. Most of the urgent admissions from the PED are neonates with viral infections, so we suggest that this finding was primarily related to the reduced spread of seasonal respiratory viruses 8,11 …”
Section: Discussionmentioning
confidence: 87%
“…The protective role of breastfeeding against bronchiolitis is particularly relevant during actual coronavirus disease 2019 (COVID-19) pandemic. In 2020, a dramatic reduction in RSV bronchiolitis hospitalization was reported worldwide, coinciding with the spread of SARS-CoV-2 infection [ 70 , 71 , 72 ]. The most accredited hypothesis to explain this uncommon finding was that the strict adoption of non-pharmaceutical interventions to contain SARS-CoV-2 diffusion (including handwashing and social distancing) also reduced the circulation of other infectious agents, such as RSV [ 71 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%
“…In 2020, a dramatic reduction in RSV bronchiolitis hospitalization was reported worldwide, coinciding with the spread of SARS-CoV-2 infection [ 70 , 71 , 72 ]. The most accredited hypothesis to explain this uncommon finding was that the strict adoption of non-pharmaceutical interventions to contain SARS-CoV-2 diffusion (including handwashing and social distancing) also reduced the circulation of other infectious agents, such as RSV [ 71 ]. Unfortunately, this reduction was only transient, with subsequent rebound during the fall and winter seasons in 2021–2022 [ 72 , 73 , 74 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%